The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.crwh.2018.e00088
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and laparoscopic management of a 5-week ectopic pregnancy in a rudimentary uterine horn: A case report

Abstract: Uterine anomalies result from the failure of complete fusion of the Müllerian ducts during embryogenesis. A unicornuate uterus with a rudimentary horn is the rarest anomaly and results from the failure of one of the Müllerian ducts to develop completely and an incomplete fusion with the contralateral side.Diagnosis and surgical management of a 5-week ectopic pregnancy in a non-communicating rudimentary horn in an 18-year-old nulliparous woman in whom this congenital uterine anomaly was previously unknown are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
(14 reference statements)
2
6
0
Order By: Relevance
“…5 This method improves operative morbidity and chances of intraoperative hemorrhage but delays definitive management. There are case reports in literature wherein they have removed the rudimentary pregnant horn successfully without prior medical management 16 similar to ours. We did a primary surgical excision of the uterine horn with live fetus in situ.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…5 This method improves operative morbidity and chances of intraoperative hemorrhage but delays definitive management. There are case reports in literature wherein they have removed the rudimentary pregnant horn successfully without prior medical management 16 similar to ours. We did a primary surgical excision of the uterine horn with live fetus in situ.…”
Section: Discussionsupporting
confidence: 76%
“…There are case reports in literature wherein they have removed the rudimentary pregnant horn successfully without prior medical management 16 similar to ours. We did a primary surgical excision of the uterine horn with live fetus in situ.…”
Section: Discussionsupporting
confidence: 75%
“…Upon diagnosis of a pregnancy in a rudimentary horn, the standard treatment involves immediate excision of the pregnant rudimentary horn for avoiding recurrence of pregnancy, removing the cause of dysmenorrhea, and preventing possible endometriosis [ 4 ]. In recent years, laparoscopic surgery has been the standard treatment for rudimentary horn pregnancy in hemodynamically stable patients [ 7 , 9 ]. During resection of a pregnant-rudimentary horn, bleeding is a major surgical risk because the pregnant uterus has abundant blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in diagnostic imaging modalities, such as ultrasound and magnetic resource imaging (MRI), have made it possible to diagnose these pregnancies before occurrence of rupture [ 7 , 8 ]. Early diagnosis can help in performing laparoscopic surgical treatment before rupture [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 10 ] To treat these cases, emergency laparotomy is performed. Apart from detecting hypovolemic shock,[ 11 12 13 14 15 16 17 ] patients frequently have abdominal pain,[ 7 11 13 14 15 16 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 ] but some reports have indicated that only 8% of rudimentary horn pregnancies (RHPs) are diagnosed before the symptoms appear. [ 44 ] Sufficient knowledge seems necessary to detect NCRHP during early obstetric screening.…”
Section: Introductionmentioning
confidence: 99%